Lived Experiences of the Staff Nurses during First Six months of their Employment in a University Hospital, Kavre - Shrestha, S; Joshi, S (Journal of Nepal Health Research Council, 2015)
Background: Nursing is a profession within the health care sector focused on the care of individuals, families, and communities so they may attain, maintain, or recover optimal health and quality of life. Role transition is the naturalphenomena among the professionals; however, the transition of newly graduated nurses into clinical practice is commonly perceived as stressful.Methods: It is a phenomenological qualitative study. By adopting purposive sampling technique, 6 nurses were recruited in the study. In-depth interview, audio tape and field notes were maintained to collect data. Nursing leaders and nursing superintendent were also involved to get supplement data via interview and focus group discussion.Results: Beginning a new job was really stressful to the new nurses. Feelings of inadequacy, fear of making errors at work, lack of competency and confidence and sudden loss of supervision from the instructors were the common sources of the stress. Four major themes; stressful initial days, leaving the nest, supporting work environment andhierarchical work pattern were emerged. The new graduates require formal orientation program, opportunities for professional development, provision of preceptors during initial days, warm and welcoming attitude among the seniors and supportive environment to help them easing a role transition.Conclusions: In order to retain and recruit new nurses the findings obtained through triangulated data need to keep in mind by the nursing administrators, educators and managers in a health care setting. And this in turn ultimately results in enhanced patient care in the health care setting.Â Keywords: employment; experiences; role transition; staff nurse.